Zachodni ‘feature’ radiowy na przykładzie amerykańskiej audycji „My Lobotomy” - Kowalska, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article consists of two parts. In the first, I analyse the relations between reportage and the feature. There are differences in the definitions of the two genres, in statements by researchers, and in the Polish and western European understanding of the feature and reportage. The main element in Polish radio documentaries is authenticity, while in the feature truth is mixed with fiction. An example of work with a mix of authentic characters and fiction is My Lobotomy by Dave Isay and Piya Kochher. In second part of the article, I focus on an analysis of this American feature. In my opinion, the most interesting aspect is the relation between the authentic, spontaneous reactions of the main characters and the narrative parts, which are read.